Optimization and characterization of gastroretentive floating drug delivery system using Box-Behnken design. (December 2013) - Rapolu, Kishore; Sanka, Krishna; Vemula, Praveen Kumar; Aatipamula, Vinaydas; Mohd, Abdul Bari; Diwan, Prakash V.
Abstract : Context: One among many strategies to prolong gastric residence time and improve local effect of the metronidazole in stomach to eradicate Helicobacter pylori in the treatment of peptic ulcer was floating drug delivery system particularly effervescent gastroretentive tablets. Objective: The objective of this study was to prepare and evaluate, effervescent floating drug delivery system of a model drug, metronidazole. Methods: Effervescent floating drug delivery tablets were prepared by wet granulation method. A three-factor, three levels Box-Behnken design was adopted for the optimization. The selected independent variables were amount of hydroxypropyl methylcellulose K 15M (X1 ), sodium carboxy methylcellulose (X2 ) and NaHCO3 (X3 ). The dependent variables were floating lag time (YFLT ), cumulative percentage of metronidazole released at 6th h (Y6 ) and cumulative percentage of metronidazole released at 12th h (Y12 ). Physical properties, drug content, in vitro floating lag time, total floating time and drug release behavior were assessed. Results: YFLT range was found to be from 1.02 to 12.07 min. The ranges of other responses, Y6 and Y12 were 25.72 ± 2.85 to 77.14 ± 3.42 % and 65.47 ± 1.25 to 99.65 ± 2.28 %, respectively. Stability studies revealed that no significant change in in vitro floating lag time, total floating time and drug release behavior before and after storage. Conclusion: It can be concluded that a combination of hydroxypropyl methylcellulose K 15M, sodium carboxy methylcellulose and NaHCO3 can be used to increase the gastric residence time of the dosage form to improve local effect of metronidazole.